WORDS THAT TEACH: A SPEECH ACT ANALYSIS OF TEACHER -STUDENT DIALOGUES IN DANGEROUS MINDS (1995) - Andi Muh. Abrar Mattangkilang; Sukardi Weda; Harnita Rosalia (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study focus on the dialogues between teachers and students in the movie "Dangerous Minds" (1995) to determine the types of illocutionary acts and how they operate as "Words That Teach". Descriptive qualitative method with pragmatic approach has been applied, in which the framework used in this study is the classification of illocutionary acts by Searle. The dialogue extracts selected for analysis have been taken from the original movie script using documentation technique, and they have been analyzed using the stages of qualitative data analysis which include data condensation, data display, and drawing conclusions as suggested by Miles, Huberman, and Saldaña. Four types of illocutionary acts have been identified in the dialogues analyzed including directive, representative, expressive, and commissive illocutionary acts. Among these acts, the most frequent type is the directive and representative act, while declarative acts were not found in the data. The role of these acts in serving as "Words That Teach" through four pedagogical roles teaching values, shaping attitudes, motivating students, and building character. The results demonstrate that language in classroom interaction, whether in real settings or fictional representation, serves not only as a communicative tool but also as a meaningful instrument for students' intellectual, emotional, and moral development. This study contributes to pragmatic and film studies by highlighting the educational value of dialogue in educational cinema.Keywords: Speech act, Illocutionary Act, Words That Teach, Dangerous Minds, Film Dialogue